Well Formed Clinical Practice Ontology Selection - Mendes, David (2012)
We show how carefull shall an ontology selection process be in the specifig sub-domain of healthcare practice. This Ontology shall be well suited to reason about the clinical practice for it has to be based upon current Semantic Web techniques. Namely reasoners over OWL DL ontologies have to handle the choosed ontology in such a way that the representational capabilities go hand-in-hand with adequate computability. We present the choice of ontology with all the theoretical considerations that have to be taken and show why the CPR ontology is the best suited for our enrichment/population endeavours.